Analysis of Sharia Banking Compliance and Compliance in Implementing Sharia Economic Principles on the Murabahah Bil Wakalah Contract: A User's Perspective on Good Corporate Governance - Yuhda, Ahmad Sabili; Yanti, Nursantri; Aslami, Nuri (Universitas Alma Ata, 2024)
Good Corporate Governance (GCG), user trust and satisfaction, policy development, and improving sharia banking practices. Research problems in the analysis of the obedience and compliance of Islamic banking in implementing the principles of Sharia economics in the murabahah bil wakalah contract from the perspective of good corporate governance (GCG) users can involve several challenges and key questions. Data and information limitations, implementation variability difficulties in measuring obedience, uneven GCG compliance, differences in sharia interpretation influence of regulations and policies, user satisfaction and transparency, challenges in performance appraisal. The research method used is a qualitative approach, namely the content of article analysis from the google scholar database. The content of the article analysis was carried out to obtain a mapping of the main theme related to Islamic banking compliance in implementing the principles of Islamic economics discussed in the google scholar database in a certain period. After the selection of the next article will be analyzed by reading the contents one by one. The results of the research found that there are still many Islamic banks that use GCG that have not complied with and obeyed the principles of Sharia economics according to the fatwa DSN-MUI, especially in the Murabahah bil Wakalah contract. The purpose of the research carried out in writing this article is to analyze the obedience and compliance of Islamic banking in implementing the principles of Sharia economics, Conclusion Islamic banking that implements the GCG system still does not fully implement the principles of Sharia economics related to the DSN-MUI fatwa regarding the murabahah bil wakalah contract to avoid transactions that contain elements of maghrib to increase customer public trust in Islamic banking.